Thin-film solar converters based on the p-Cu₁.₈S/n-CdTe surface-barrier structure - Bobrenko, Yu.N.; Pavelets, S.Yu.; Semikina, T.V.; Stadnyk, O.A.; Sheremetova, G.I.; Yaroshenko, M.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
A surface-barrier structure with the transparent p-Cu₁.₈S component was used to make thin-film polycrystalline n-CdTe-based solar converters. Cadmium telluride was grown on CdSe substrates using the quasi-closed volume technique through a graded-gap CdSexTe₁₋x interlayer. A multilayer p-Cu₁.₈S/n-CdTe/n-CdSe/Мо structure was prepared. It makes it possible to increase the degree of structural perfection of thin photosensitive n-CdTe layers without application of additional high-temperature treatments, as well as to obtain an ohmic back contact without some additional doping of CdTe. The quantum efficiency spectra and critical parameters of solar converters have been presented. The prospects for application of polycrystalline n-CdTe in solar power engineering have been discussed.